La reincidencia en el consumo de sustancias en los adolescentes que recibieron tratamiento durante el año 2016-2017 de la Estación Municipal de Auxilio Terapéutico Juvenil N° 2, periodo 2017-2018 - Castillo Prado, Gladys Alexandra (2018)
The present research work has been developed with the participation of former residents from "Estación Municipal de Auxilio Terapéutico Juvenil Nº2", who were in rehabilitation during 2016 and 2017 due to problems of subtances consumption such as alcohol and other drugs, in order to stablish how many former residents rehabilitated and how many relapsed, pointing out their reasons, and how much they know of the treatment they received. This research work consists of a desciptive study using, as the research method an interview directed to the residents as well as the institution's staff, that were previusly validated, and the information gathered was analyzed and transcribed. The group of study consisted of 78 former residents and 7 members of the staff. It showed that former residents had a high index of relapse in the substance consumption, with marihuana being the most common, followed by alcohol and some other substances, due to many reasons, being the family factor the most mentioned. The results also showed that the treatment provided by the institution is integral, which includes medical, psychological, experiencial, educational and occupational, with the exception of isolated cases where pharmacological treatment by a particular psychiatrist was needed to determine whether or not the patient's treatment was finished at the Municipal Station. Key words: rehabilitation, consumption, treatment, relapse.